1969
DOI: 10.1080/14640746908400231
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Angular Subtension

Abstract: The confusion arising over judgements of the sizes of angular forms is described. Three experiments are reported. In the first, the apparent-sizes of acute and obtuse angles are estimated. In the second, judgements of the sizes assumed by upwardand downward-and left-and right-facing angles are compared. The third experiment is concerned with tactile reproduction of angles of specified sizes. In discussion an attempt is made to clarify the logical and empirical problems involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

1971
1971
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…This latter overall relationship remains constant, but the absolute differences are reduced at either end of the range, in comparison with the band of 47 to 135 deg. This corresponds to the position in Fisher's (1969) Fig. 4, with the differences in his case narrowed around 90 deg by the nonperceptual consequences of using 5-deg intervals and a free-estimation response mode (see also Chapanis, 1951).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This latter overall relationship remains constant, but the absolute differences are reduced at either end of the range, in comparison with the band of 47 to 135 deg. This corresponds to the position in Fisher's (1969) Fig. 4, with the differences in his case narrowed around 90 deg by the nonperceptual consequences of using 5-deg intervals and a free-estimation response mode (see also Chapanis, 1951).…”
Section: Resultsmentioning
confidence: 99%
“…A randomizing procedure determined whether the vertex was up/down, right/left, or a combination of these for diagonally presented angles. Fisher (1969) had reported that the direction of the vertex had no effect on judgments obtained in his situation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The logical flaw in this procedure has been pointed out by Fisher (1969) (italics in original): "Suppose, for example, that when shown a 40°angle a subject judges it to be one of 45°. When attempting to reproduce it he will construct two lines which he believes to represent an angle of 45°.…”
mentioning
confidence: 99%
“…The law essentially expresses the amount of illusion as a function of the size relationships of the stimulus figure and predicts relative values for the qualitative characteristics of illusion functions. One instance of the law concerns the perceptual enlargement or overestimation of an acute angle (Wundt, 1896;Berliner & Berliner, 1948;Fisher, 1969). The overestimation of an acute angle (0) is given by…”
mentioning
confidence: 99%